Towards energy efficiency of interdependent urban networks. (2016) - Alonge, Giuseppe; Ciancamerla, Ester; Mastrilli, Alberto; Minichino, Michele; Nicotra, Angelo; Ranno, Marco; Reali, Maurizio; Regina, Pasquale
Modernised urban networks will constitute the backbone of smart cities. Modernisation of urban networks is far from being realised and an extensive use of comprehension, and of models at adequate level of granularity, is needed. The paper proposes a cross-domain methodology to represent and evaluate energy efficiency of interdependent urban smart grid, gas and water networks. Models use domain simulators to faithfully represent each physical network, and transversal simulators to represent the three interdependent physical networks, their interdependencies and to compute energy efficiency indicators. Models built by domain simulators are also used to validate models built by transversal simulators. An actual smart grid connected to photovoltaic plants of different power and location is modelled and its efficiency indicators are analysed and discussed. The grid model will be then interconnected with basic gas and water network models to investigate the impact of their interdependencies on energy efficiency indicators.